Seasonal Variation in Proximate Composition and Fatty Acid Profile of Grey Triggerfish (Balistes capriscus) Captured Along the Coast of Portugal. Issue 5 (2nd April 2013) - Simões, Tiago; Carvalho, João; Sousa, Ana; Lemos, Marco F.L.; Gil, Maria M.; Pedrosa, Rui; Tecelão, Carla
Abstract Proximate composition (ash, moisture, total protein, and fat contents) and fatty acid profile of Balistes capriscus (grey triggerfish) were assessed over a 6‐months period (April to September, 2011) in animals captured along the coast of Peniche (Portugal). High protein (18.9% to 21.4%) and low lipid (0.5% to 0.8%) contents were determined. The highest lipid level was found in June‐captured animals. High proportions of n‐3 polyunsaturated fatty acids (n‐3 PUFA) were observed (53.87 ± 2.00%) together with substantial quantities of oleic acid (27.58 ± 1.09%) and palmitic acid (16.52 ± 0.93%). Docosahexaenoic acid accounted for 77% of the total PUFA and was 7 times more abundant than eicosapentaenoic acid, and the n‐3/n‐6 ratio was 7.2. Gender did not influence lipid levels and the fatty acid profile, but seasonal variations were observed for PUFA and monounsaturated fatty acid contents. Overall, the nutritional properties of this underexploited species may be comparable to those of other lean fish species with higher economic value.